Investigating the effects of knee valgus orthosis on knee joint contact forces among subjects with knee osteoarthritis: A case series study - Mohammad Taghi KARIMI; Mahmood BAHRAMIZADEH; Hanieh KHALILIYAN; Majid ANSARI; Kavita BATRA; Aanuoluwapo AFOLABI; Olayinka ILESANMI; Lukasz SZARPAK; Hicham KHABBACHE; Gabriella NUCERA; Aldo SITIBONDO; Farhad GHAFFARI; et al. (Journal of Health and Social Sciences)
Introduction: An increase in knee joint loading exacerbates the symptoms of knee joint osteoarthritis (OA). One of the conservative treatments used for subjects with knee OA is knee valgus orthosis, which is used to decrease the loads on knee joints. The aim of this study was to determine the effects of a new design of knee orthosis on joint contact force and muscle force in subjects with knee OA. Methods: Ten subjects with knee OA were recruited for this study. A motion analysis system with seven high-speed cameras and a Kistler force plate were used to record the motion of the subjects in walking and the forces applied on the leg. We used OpenSIM software to determine the knee joint contact force during walking, with and without the orthosis. Results: The knee orthosis decreased the peaks of the vertical component of knee joint contact forces (p < 0.05). Moreover, it did not influence walking speed. The use of the orthosis decreased the extension moment of the knee joint and the peaks of the forces produced by the muscles surrounding the knee joint. Discussion: The use of this orthosis decreased the knee joint contact forces. This suggests that the orthosis could be used to alleviate the symptoms of knee OA. Orthosis can be incorporated into the clinical management of subjects with knee OA by medical practitioners.